QUESTIONING STRATEGIES AND REINFORCEMENT FOR ENHANCING EFL STUDENTS' VERBAL RESPONSES - IRMA GHASANI, BETARI (English Literature Department, Faculty of Economics, Law, and Humanities, 2023)
In the classroom, for teachers, being able to communicate well is essential to stimulate students’ skills, especially in speaking. For English as a Foreign Language (EFL) learners, however, a spoken interaction or dialogue provides a challenge that must be overcome. Many studies map out that teachers’ strategies for questioning their students have a strong effect on students’ ability to speak. Using questions allows teachers to explore the material in greater depth and check students' understanding as they master the material discussed in class. Furthermore, motivation also plays an important role in evoking student responses when learning to speak. As a motivational example, reinforcement plays an important role in helping students speak. Most studies related to questioning strategies in classroom discourse focus only on strategies. However, while knowing student interest in lectures is important, the combination of questioning strategy and motivation is rarely implemented. In this regard, this study combines questioning strategies and reinforcement to get a clearer picture of students' verbal responses by asking teachers questions. The results indicate a high incidence of questioning strategy decomposition and language reinforcement during the teaching and learning process.